(untitled) (Journal of Civil Engineering Researchers, 2026)
The rapid increase in concrete waste has emerged as a significant global environmental challenge. In addition, the depletion of natural resources commonly used in concrete production highlights the necessity of adopting sustainable alternative materials. The incorporation of recycled aggregates in new concrete is considered an effective approach to reducing environmental degradation and preserving natural resources. This study aims to evaluate the influence of replacing natural coarse aggregates with recycled coarse aggregates on the properties of fresh and hardened concrete. For this purpose, three replacement levels—0%, 50%, and 100%—were examined. A slump test was conducted to assess the workability of fresh concrete, while 28-day hardened samples were subjected to compressive strength, direct tensile strength, and indirect tensile (splitting) strength tests. The results indicate that increasing the replacement ratio of recycled aggregates leads to a notable reduction in compressive strength as well as direct and indirect tensile strengths. Furthermore, higher proportions of recycled aggregates significantly decreased the slump value, thereby reducing the workability of fresh concrete. These findings suggest that although the use of recycled aggregates is environmentally advantageous, their incorporation requires careful technical considerations in concrete mix design.